HEGEMONY OF LANGUAGE AS REFLECTED IN BURNETT’S A LITTLE PRINCESS - Eka Kurniawati; Anwari (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This research is intended to find out the form of the hegemony of language that is conducted by the ruling class over the subaltern people in the Novel A Little Princess. This research also explains the causal factor and its effects on the characters of Burnett’s novel in the Victorian Era. The researcher uses Gramsci’s concept of hegemony. Hegemony is the predominance obtained by consent rather than the force of one class over other classes. This research applies to library research because the corpus is a novel entitled A Little Princess. Besides that, this research is a concept analysis. The researcher explains the object and relates it to concepts, theories, or other relevant sources. It can be concluded that the ruling class conducts the hegemony of language because there is a diamond mine. The hegemony of language in this novel brings many impacts. They are: French becomes a nobility language in the Select Seminary environment, the classification of society as two classes (aristocratic and pariah class), a snobbish attitude, unfair and arbitrary attitude towards pariahs, and the emergence of resistance.